Curriculum Modification to Improve Counting Fraction Ability on Slow Learner Children - Prawira, Arif; Misdayani, Misdayani; Siagian, Ira Ocktavia; Arifin, Tazul; Rochyadi, Endang (Journal of ICSAR, 2024)
Not every student gets a learning system that suits their abilities. Therefore, teachers need to know the stages of modifying the curriculum so that it is according to the abilities of students. This study aims to find the stages of modifying the Merdeka Curriculum at the elementary school level in the form of a learning program design in mathematics into fractional material that is adapted to the needs of students with learning disabilities. The research was conducted using the Research and Development research method, the development model carried out in this study used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in this study were one fifth-grade teacher and one slow learner who was in fifth grade at SDN 195 Isola, Bandung City. The results of the research found that after the modification of the curriculum, the subject's math score increased from 29 to 100. In addition, the subject dared to answer questions when asked to repeat the elements of fractions, another impression that the subject did not feel distinguished in giving teaching material.